134 Utility of 24 hour ambulatory blood pressure monitoring (ABPM) in patients with orthostatic hypotension (OH) seen at a syncope clinic. (17th July 2020) - Reid, George; Arnott, Andrew; Godwin, Jon; Anderton, Lesley; Mitchell, Lara
Abstract : Background: Orthostatic hypotension (OH) is a disabling condition resulting from a sustained reduction in blood pressure (>20 systolic or 10 diastolic) within 3 minutes of standing. It is a common cause of syncope and is a marker of increased risk of mortality and of cardiovascular disease. OH is often secondary to medication. Patients with concurrent hypertension experiencing syncope present a complex management dilemma where a balance must be established between symptom burden and risk of cardiovascular disease. The current European Society Cardiology (ESC) syncope guidance suggests ABPM should be used in patients with 'autonomic failure' to assess nocturnal hypertension or drug-induced hypotension. Could this be improved with further explicit criteria on which patients should be monitored and interpretation of results? Purpose: The aim of this study is to review the use of 24 hour ABPM in OH within a tertiary referral syncope clinic. Methods: A retrospective analysis was performed electronically for patients with a final diagnosis of OH seen in the syncope clinic between March 2017 and May 2019. We collected data on comorbidities, medication history, physical mobility, clinic blood pressure measurements, 24 hour ABPM results (if performed) and medication changes. Comparisons were made between patients who had ABPM and those who did not. Statistics were calculated using Fisher's Exact Test (2 tailed). Results: 119 patients had a final diagnosis of OH in the study period. 45 had ABPM, 74 did not. The ABPM group had a significantly higher proportion of diagnosed hypertension at 51.1% vs 23% (p=0.0025). A similar proportion of patients in both groups had medication changed however the ABPM group were significantly more likely to have antihypertensive therapy added at 19.4% vs 1.8% (p=0.0053). Discussion: In a secondary care syncope clinic ABPM is more likely to be performed in patients with a history of hypertension. Despite OH often being due to medication, the need for adequate BP control is important in reducing risk of cardiovascular morbidity. Current ESC guidance targets BP for those aged 65 and over to be under 139/79 if tolerated. In symptomatic OH patients it is crucial to establish accurate blood pressure measurements in order to assess need for additional therapy. This can be provided by a 24 hour ABPM. Management of these patients must balance their symptoms with their comorbidities and target blood pressure control. Conclusion: Using 24 hour ABPM in OH patients can aid clinical decision making in the sub-group with hypertension to guide the need for alteration/ addition of antihypertensive therapy. Conflict of Interest: nil